The Effects of Facial Lipografting on Skin Quality: A Systematic Review - van Dongen, Joris A; Langeveld, Mirte; van de Lande, Lara S; Harmsen, Martin C; Stevens, Hieronymus P; van der Lei, Berend (Plastic and reconstructive surgery (1963), 2019)
Autologous lipografting for improvement of facial skin quality was first described by Coleman in 2006. The current dogma dictates that adipose tissue-derived stromal cells that reside in the stromal vascular fraction of lipograft contribute to skin rejuvenation (e.g., increased skin elasticity), a more homogenous skin color, and softening of skin texture. Nowadays, many studies have been reported on this "skin rejuvenation" effect of autologous fat grafting. This systematic review was undertaken to assess the efficacy of autologous lipografting on skin quality. The MEDLINE, Embase, Cochrane Central, Web of Science, and Google Scholar databases were searched for studies evaluating the effect of autologous lipografting on facial skin quality (May 11, 2018). Outcomes of interest were skin texture, color, and elasticity in addition to histologic outcomes and number of complications. Nine studies were included, with 301 patients treated in total. No meta-analysis could be performed because of heterogeneity of the metrics and outcomes. Eight studies reported increased skin elasticity; improvement in skin texture; and a more homogeneous skin color after treatment with lipografting, cellular stromal vascular fraction, or nanofat. One study reported no increased skin elasticity after lipografting. Histologic improvement was seen after lipografting and adipose tissue-derived stromal cell injections. However, in general, the level of evidence of the included studies was low. No serious complications were reported. Autologous facial lipografting and cellular stromal vascular fraction and adipose tissue-derived stromal cell injections hardly seem to improve facial skin quality but can be considered a safe procedure.